Implementation of Telegram Bot Notification on Network Device Monitoring System - Andriani (SCOPUS ID: 57208011426), Ria; Sa’di, Ahmad (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
The development of social media is currently progressing rapidly with various features and services that are distinctive and have selling value. With the existence of social media, access to information becomes faster and easier, available anytime and anywhere. Telegram is a social media platform widely used by users in Indonesia. PT XYZ is a company involved in rural internet infrastructure development, web, and apps development. The Mikrotik Router owned by PT XYZ has issues in monitoring its devices, such as sudden disconnection of connections and general router conditions that can have fatal consequences if not monitored in real-time, as it relates to customer satisfaction using PT XYZ's network. Since network admins or assigned personnel cannot continuously monitor from the NOC office computer due to working hours, employee leaves, or having schedules outside, they need a quick way to obtain real-time information about the Mikrotik router's condition. This study aims to design a monitoring system using a Telegram Chat Bot to receive monitoring results from The Dude for Mikrotik routers, which can provide information related to activities or issues that occur with the Mikrotik router. The final outcome of this study will facilitate the reception of information when there are connection problems and physical conditions of Mikrotik for PT XYZ technicians.